Village Financial Performance Model in the Village of Wadung Asri, Waru Sub-District, Sidoarjo District - May Retno Adiwaty (Future Science)
Reform of management of local or village finance after the Act No. 22 of 199 and Law No 25 in 1999. As a concrete effort, the government issued a regulation on the Management and Accountability of regional finance. Wadung Asri is the best village in Sidoarjo in the financial management of village and district. Sidoarjo is an example of Successful Regional Autonomy in East Java. In this research, it is explained about Budget Realization Report of Wadung Asri village in 2015 to 20016 and how its performance from the report. Observing the village's original income (PAD), the village of Wadung Asri PADes is 7.78%. if using UGM standard then Wadung Asri village is not autonomous because it is still under 10% so Wadung Asri Village still rely on outside fund that is equal to 92,21% revenue from transfer. By 2015 in 2016, the original income of 6.94% actually decreased by the previous year. Fund from outside of the transfer of 93.05% is also larger than the previous year, thus the financial performance of the village in the village of Wadung Asri is not good. In fact, the budget defisit amounted to Rp 20,641,462.61 or 1.48% of the expenditures closed with the proceeds from the sale of village land.